Sprawiedliwość transformacyjna, filozofia prawa i rozliczanie przeszłości przez demokratyczne państwo prawa - Snarski, Tomasz (Pamięć i Sprawiedliwość, 2010)
The article raises the issue on the transformational justice relating to the theory of policy towards the past. The legal system, which can not only allow to exact compensation for the harmful history but also be used to oppose it actively, played a very important role in the process of coming to terms with history. To put it another way, in order to comprehend how the instrument of law was used by the state in the transformational justice process, one should refer to the jurisprudence. An overview of the post-war era philosophical and legal debate over the general problem of crimes against humanity is considered by the author to be a starting point to formulate a general concept of the necessity of referring to the philosophy of law in any process of settling accounts with the past. Furthermore, the other countries’ experience which went through the transformation process, as well as their scholarly achievements, may also be of invaluable help to Poland with its difficulties in solving problems with the difficult past.